THE EFFECT OF USING RED BRICK WASTE MIXED WITH ASPHALT CONCRETE WEARING COURSE - DANANG ARIS MUNANDAR; SAHAT MARTUA SIHOMBING; LYDIA DARMIYANTI (CV KULTURA DIGITAL MEDIA, 2024)
Flexible pavement is a road construction that uses aggregate and asphalt as a binder to create a strong road layer. This pavement is able to withstand and distribute vehicle loads to the underlying soil layer and is often used on roads with reduced loads and traffic. This study used AC 60/70 penetration asphalt, which is suitable for hot climates and high traffic. With the large amount of red brick waste in Indonesia, this study utilizes the waste as a partial substitute for fine aggregate in the laston mixture. The title of this study is